Deskripsi Penalaran Siswa dalam Pemecahan Masalah Matematika pada Pokok Bahasan Barisan dan Deret Ditinjau dari Kemampan Awal - Irma Sulistiawati; Nurdin Arsyad; Ilham Minggi (Issues in Mathematics Education (IMED), 2019)
This study aims to describe students' reasoning in mathematical problem solving on the topic sequences and series viewed by prior knowledge. This type of research is descriptive qualitative. By using purposive sampling technique, then, the research subjects were selected as many as 2 students of class XI MIPA, one of the high schools in Makassar. The data collection technique uses test methods and interviews then through three stages of data analysis, namely data reduction, data display, and drawing conclusion. The results showed that the reasoning process of high-ability students was to associate the concepts and knowledge they had, gather evidence by mentioning things that were known and asked, linking the formulas that were already owned with the problems faced, identifying concepts used to solve problems, revealing reasons in explaining the steps in carrying out problem solving. And drawing conclusions explains the concepts used from the problem. While the reasoning process of low-ability students is to mention things that are known and asked and students cannot make any conclusions after solving the problem. This is because students have not fully understood the problem, students are not used to correcting the answers obtained, and students are not used to writing final conclusions.